Out in Front: Government Regulation of Television in Malaysia: Government Regulation - Kitley, Philip; Nain, Zaharom (Television, Regulation and Civil Society in Asia, 2002)
Modern Malaysia was established in 1963 following a drawn-out struggle against British interests which had occupied territory on Penang and Singapore and the Straits of Malacca in 1786, 1819 and 1824 respectively. In 1867 these outposts came under the control of the British Colonial Office and were governed as a Crown Colony. Although Britain did not directly colonise the Malay States, which remained legally autonomous, it imposed effective administrative control over Malaya and the Borneo territories from the late 1870s until the Japanese occupation in 1942.
Num Pages: 2
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; Australie (lieu de production du savoir); Malaisie (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Muslims on Television: News and Representation on Satellite Channels - Sengupta, Roshni (Television in India: Satellites, Politics and Cultural Change, 2008)
For any exposition of the television news medium to hold merit itbecomes imperative to glide into the past to recover its earliest antecedent –the newsreel. Newsreel presentation involved an intimate relationshipbetween its producers and events that print reporters had never faced: it wasentirely dependent on pictures that required the camera to be in positionbefore they unfolded (Montague, 1938: 49). Thus, the early producers ofnewsreels discovered that at times when there was a lack of any worthwhileor pictorial news it was possible to create it. It was also possible to ‘experiment’ with news. Newsreels in the United States, therefore, experi-mented with everything: news borrowed from newspapers, studies by collegeprofessors, animated diagrammatical representations of a volatile stockmarket, and so on. Since newsreels were exhibited before drama perfor-mances and film shows in theatres, a great degree of dramatisation andsensationalism was not deemed out of place. They too became part of theentertainment media.
Num Pages: 19
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Inde (corpus analysé); Pologne (lieu de production du savoir); _Nettoyé

The Saffron Hues of Gender and Agency on Indian Television - Chakrabarti, Santanu (Channeling Cultures: Television Studies from India, 2014)
This chapter explores the contradiction between two sets of responses to the so-called K-serials, earlier, largely condemnatory ones, and more recent, largely laudatory ones. The chapter aims to understand this contradiction and resolve it. It does so by showing how K-serials were a definitive break at that specific point in time from the ones that had immediately preceded them, especially in bringing to the fore the bahu (daughter-in-law) of Hindu urban extended families. It traces the complex place of gender in the discourse of the Hindu right and explores the strong debt that the K-serials owe to the ideological constructions of the woman and the family by Hindu nationalism. It argues therefore that the consequences of celebrating agency and empowerment in a right wing milieu-as some recent scholarship has done-ends up advocating for a limited and exclusionary form of female agency.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Copied from Without and Cloned from Within: India in the Global Television Format Business - Thomas, Amos Owen; Kumar, Keval J. (Television Across Asia: TV Industries, Programme Formats and Globalisation, 2003)
Television programme format adaptation is becoming an increasingly signiﬁcant phenomenon in India as it is in many other countries with an active domestic television industry. Some obvious successes stand out in recent years, such as Kaun Banega Crorepati, the licensed adaptation of Celador’s global format success Who Wants To Be A Millionaire?, and C.A.T.S., a licensed Hindi version of the US detective series Charlie’s Angels. However, sensitivity to local cultural nuances has been critical to their popular reception by Indian audiences. Yet despite a few high-proﬁle licensed adaptations or copycatting, there are far more instances of unlicensed adaptations or cloning, sometimes subtle, other times not.
Num Pages: 16
Keywords: 1-TV; 2-Analyses formalistes; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Inde (corpus analysé); Inde (lieu de production du savoir); Suède (lieu de production du savoir); _Nettoyé

Gender, Ideology and Latin American Children's Animated Television - Gonzalez-Rodriguez, Milton Fernando (Children, Youth, and International Television, 2022)
Animation allows for the creation of mediatic spaces that strengthen prevailing ideologies of masculinity and femininity. Manhood seems to operate as a key point of reference in the creation of televised animation across Latin America, especially by elevating certain heroic cultural narratives. Through a review of 21 television series, produced between 2008 and 2018, this chapter examines the portrayals of femininity and masculinity in some of the most widely broadcast animated series from the region. As a norm, Latin American illustrators adhere to the tradition of depicting female figures as secondary characters, as leading characters with a certain degree of autonomy, or as subaltern, considerate, and supportive figures. By contrast, male figures are portrayed as strong, daring, independent, and primary characters, often destined to lead their families and communities, and save their weaker friends that are typically female characters.
Num Pages: 11
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Argentine (corpus analysé); Belgique (lieu de production du savoir); Brésil (corpus analysé); Chili (corpus analysé); Colombie (corpus analysé); Mexique (corpus analysé); Pérou (corpus analysé); _Nettoyé

Representations of Childhood and “Modes of Address” in Palestinian and Pan-Arab Programs for Children - Awan, Feryal (Children, Youth, and International Television, 2022)
This chapter explores the ways in which the portrayal of children in Palestinian screen content compares with the positioning of children in leading pan-Arab children’s channels. Using critical discourse analysis, it compares the definition and representation of childhood in three Arabic language texts (two magazine shows and one animation), and examines the ways in which the texts construct narratives of childhood and whether they reproduce or challenge hegemonic definitions of childhood. The chapter analyses the language used to address the child audience and the ways in which adult–child relations are depicted. The chapter concludes that while there are some characteristics unique to Palestinian programming, the positioning of children and the “modes of address” are similar in all three programmes, and there are common assumptions and idealizations of childhood. However, there is some evidence that the Emirati animation analysed challenges dominant (adult-generated) definitions of childhood present in Arab societies by presenting childhood as a dynamic space of empowerment
Num Pages: 16
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Pakistan (corpus analysé); Royaume-Uni (lieu de production du savoir); _Nettoyé

Bridal Anxieties: Politics of Gender, Neoconservatism and Daytime TV in Turkey - Sayan-Cengiz, Feyda (Female Agencies and Subjectivities in Film and Television, 2020)
This chapter analyzes the reflections of Turkey’s neoconservative and neoliberal politics of gender on daytime television. The focus is on Bridal House, a popular daytime TV show in Turkey which interpellates women as domestic subjects competing with other women to prove their domestic abilities, particularly the ability to navigate the etiquette of domestic consumption. Hierarchies are instigated among women through symbolic battles on “tasteful” consumption, and the marital household surfaces as a space of constant regulation where women strive to be ideal housewives. By analyzing Bridal House through a Bourdieusian framework, this chapter traces the representations of the “ideal female subject” along neoconservative and neoliberal lines, and demonstrates the ways in which symbolic violences are enacted on women in contemporary Turkey’s daytime TV culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Analysing How Zimbabwe Broadcasting Corporation (ZBC TV) and Eswatini TV (ESTV) Are Adapting to the Digital Era - Lunga, Carolyne M.; Musvipwa, Rosemary (Television in Africa in the Digital Age, 2021)
The internet has impacted on how media organisations do journalism. Many media organisations both print and broadcast now have an online presence to reach out to fragmented audiences that have migrated to online platforms. Television stations have increasingly embraced the use of digital (online) media to gain better access to their audiences in terms of content distribution and audience engagement. The rise of social media platforms such as Facebook, Twitter, YouTube and Instagram have given journalists and media organisations the ability to reach their audiences immediately, with the added beneﬁt of audience responses which come almost immediately. The use of new digital media has created platforms for news stations to share digital clips of news items or excerpts of news programmes to keep the audiences informed or enticed by the highlights.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; Eswatini (corpus analysé); Eswatini (lieu de production du savoir); Royaume-Uni (lieu de production du savoir); Zimbabwe (corpus analysé); _Nettoyé

The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves - Çetin, Berfin Emre (Cambridge Scholars Publisher, 2015)
The Paramilitary Hero on Turkish Television: A Case Study on Valley of the Wolves explores the representation and reception of nationalism and masculinity in Turkey through an examination of the popular television serial, Valley of the Wolves which has been aired on Turkish television since 2003. This detailed examination of the show demonstrates a particular discourse of nationalism, namely the Turkish Islam synthesis embedded in a gender-specific regime in which the paramilitary hero is placed at the centre. The study draws on thirty-seven in-depth interviews with viewers of the programme from different social backgrounds. These viewers read the serial from various perspectives in the light of their gendered experiences, suggesting that the relationship between text and audience is not necessarily predetermined by the former, but is rather constructed through an interdiscursive process. The book also examines the pleasures of the “contesting” readers of Valley of the Wolves, drawing on the audience interviews, and argues that critical approaches to a particular media text do not present a barrier to audience pleasures.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Women, Television and Everyday Life in Korea: Journeys of Hope - Kim, Youna (Taylor & Francis Group, 2006)
Fusing audience research and ethnography, the book presents a compelling account of women's changing lives and identities in relation to the impact of the most popular media culture in everyday life: television. Within the historically-specific social conditions of Korean modernity, Youna Kim analyzes how Korean women of varying age and class group cope with the new environment of changing economical structure and social relations. The book argues that television is an important resource for women, stimulating them to research their own lives and identities. Youna Kim reveals Korean women as creative, energetic and critical audiences in their responses to evolving modernity and the impact of the West. Based on original empirical research, the book explores the hopes, aspirations, frustrations and dilemmas of Korean women as they try to cope with life beyond traditional grounds. Going beyond the traditional Anglo-American view of media and culture, this text will appeal to students and scholars of both Korean area studies and media and communications studies.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; Corée du Sud (corpus analysé); France (lieu de production du savoir); _Nettoyé

Mediatised Culturalisation Through Television: Second-Generation Alevi Kurds in London - Emre Cetin, Kumru Berfin (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Satellite television has not only provided migrant communities with stronger ties to their home countries but also enabled second-generation migrants in particular to know more about their country of origin beyond their family ties. The aim of this chapter is to explore the ways in which Turkish television contributes towards the making of the transnational identity of the “twice minority” group of Alevi Kurds through what I call mediatised culturalisation. Drawing on 17 in-depth interviews that I conducted with the second-generation members of the Alevi Kurdish community in London in 2016, I explore the role of Turkish television in contesting the boundaries of transnational social imaginaries of the second-generation viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

From TRT to Netflix: Implications of Convergence for Television Dramas in Turkey - Yanardağoğlu, Eylem; Turhallı, Neval (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Since the1980s, the television (TV) drama has proved to be one of the most dominant formats on Turkish TV channels and occupied major slots on primetime throughout the 1990s and 2000s. As Internet penetration grew, on-demand services transformed audiences’ expectations of TV series. Internet series first became a trend on YouTube in 2013, and Netflix began broadcasting in Turkey at the beginning of 2016. Its entry to the sector triggered video-on-demand suppliers like Blu TV and Puhu TV which are digital enterprises of Doğan and Doğusṃ Holdings. Blu TV announced their first original project in 2017, Masum (Innocent), which was a big-budget series that included famous actors. In the same year, Puhu TV released their first original, Fi (Phi). Finally, Netflix launched their first original production in Turkey, Hakan: The Protector, in 2018. This chapter focuses on the implications of convergence for the production and distribution of TV dramas and considers the changes in the sector as television broadcasting shifted to new media platforms in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Continuities and Changes in the Transnational Broadcasts of TRT - Karanfil, Gökçen (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter traces the evolution of the Turkish Public Service Broadcaster with a focus on its transnationalization. Drawing parallels between the changing dynamics in politics, culture, and media in Turkey; contemporary cosmopolitan media cultures; and the continuities and changes in Turkish Radio and Television Corporation’s (henceforth TRT) identity as a public service broadcaster, I shed light on the ways in which TRT has been engaging in transnational broadcasts since the beginning of 1990s. For this I elaborate on the ways in which transnational broadcasting processes in Turkey have been influenced by media transnationalization around the world. I discuss two different incentives behind TRT’s transnational endeavors. First, I elaborate on TRT’s attempts at engaging with the Turkish diaspora around the world; later, I articulate how, in more recent years, TRT sets out to exert a Turkish cultural presence in the Middle East and North Africa (MENA) region. The chapter aims to draw a general portrait of the concept of transnational broadcasting in Turkey with a specific focus on the country’s public service broadcaster, TRT.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Televised Journalistic Documentaries of the 1990s: The Form, Content, and Historical Juncture - Çelik, Burçe (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The 1990s’ popular televised journalistic/history documentaries have played a vital role in the making of political television culture, society of political spectacle, and the production of popular history and memory in Turkey. Despite their importance, these documentaries did not attract enough scholarly attention. By focusing on arguably the most popular and impactful journalistic/history documentaries of Turkey’s history, developed by Mehmet Ali Birand in the 1990s, I will assess the role of television in teaching, telling, and writing the political history. In doing so, I will also contextualize the form and discourse of these documentary series within historical juncture of globalization and neoliberalization of television as well as the country’s political economy.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

The Regulation of Television Content in Turkey: From State Monopoly to Commercial Broadcasting and Beyond - Sümer, Burcu; Taş, Oğuzhan (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
In contrast with radio broadcasting, which began in 1927, television started remarkably late in Turkey. When the country’s sole public service broadcaster, Turkish Radio and Television Corporation (TRT), was established in 1964 and all of the radio transmitters were transferred to the Corporation, even radio broadcasting was not successfully institutionalized to catch up with its Western counterparts. For a very young Republic like Turkey, radio was an integral part of the modernization and nation-building agenda of the early ruling elite and therefore it institutionalized as a part of the machinery of the state, under very strict state control. Much known indispensable merits of autonomy and independence attributed to the historical public service broadcasting model in Europe were hardly appreciated and supported in Turkey. Television broadcasting also had its share from this negative perception and had to face similar obstructions as radio from the beginning. This chapter traces the history of content regulation in television broadcasting by situating the political controversies at the center at different times from the 1960s until today. Unfortunately, as the saying goes, there is nothing new under the sun, not in Turkey.
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Structural Changes in the Ibero-American TV Market: Concentration and Convergence against Diversity? - Mastrini, Guillermo; Leiva, María Trinidad García (The Routledge Companion to Global Television, 2019)
This chapter examines the structural changes that can be identified in Ibero-American television in the first 15 years of the 21st century. Taking as a reference the main TV markets in the region (Mexico, Brazil, Argentina and Spain) and their peculiar historical developments, a brief introduction and overview describes their characteristics, potentials and limitations, underlining their strengths, weaknesses and challenges. The analysis, framed in the globalizing phase that cultural products and services are undergoing jointly with their increased digitization, suggests two fundamental drivers of change, summarized in the notions of concentration and convergence. To conclude, policies and recommendations for action are explored, with a view to promote and protect audiovisual diversity.
Num Pages: 10
Keywords: 1-TV; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Argentine (corpus analysé); Argentine (lieu de production du savoir); Brésil (corpus analysé); Espagne (corpus analysé); Espagne (lieu de production du savoir); Mexique (corpus analysé); _Nettoyé

Global Television Formats in Africa: Localizing Idol - Nkosi Ndlela, Martin (Global Television Formats: Understanding Television Across Borders, 2012)
During the last decade, popular television formats have been replicated across the globe for local or regional consumption as program imports, adaptations, clones or imitations, raising questions on the possible ramiﬁcations of such cultural inﬂows. For Africa the international program ﬂow and the inﬂuence of Western media content has been a contentious issue for decades, underlying the cultural imperialism thesis of the 1970s and 1980s, and the centre– periphery paradigms which conceptualized the series of dependency relationships. In African media research concepts like cultural colonialism, media imperialism, neocolonialism, Americanization, homogenization, have been used to denote the unequal ﬂow and inﬂuence of Western media products in Africa. Within the framework of media globalization some scholars have even propounded a scenario of the emergency of a global culture mediated by the dominant Western media. The central issues in African media discussions have mainly revolved around the ﬂow of ﬁnished media programs and their perceived detriment to local cultures and identities. What is missing in the African research literature is the attention to television formats, a phenomenon described by Keane et al. (2002) as a vehicle for localization, since what is imported is not the content itself, but a recipe for creating a local version. Global reality format shows thus create a new picture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Afrique (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; Afrique du Sud (corpus analysé); Ghana (corpus analysé); Nigéria (corpus analysé); Norvège (lieu de production du savoir); _Nettoyé

Telenovela, an Instrument for Democracy - Eskandari, Sina (Review of European Studies, 2017)
Telenovela shapes important and highly favorite section of the television productions. The T.V. series have moved out from their traditional structure with an entertaining aspect and have been divided into different types and scopes. Taking into consideration the time and the atmosphere of dissemination which the Telenovela programs hold in T.V. antenna, there is a need to conduct studies on sociology of Telenovela more than any other times in the past. This article is an attempt to review the two subject-matters of Telenovela and Narration and their connection with democracy through sociological sporadic studies. This will also present the significance of this genre in T.V. productions at local and international discourses. Observations, field researches and library study methods have been employed in this research.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Identités diasporiques; Colombie (corpus analysé); Espagne (lieu de production du savoir); _Nettoyé